2000
DOI: 10.1002/1521-4028(200012)40:5/6<377::aid-jobm377>3.3.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

A highly homologous 68 kbp plasmid found in Vibrio vulnificus strains virulent for eels

Abstract: Vibrio vulnificus serovar E (biotype 2) strains are virulent for eels and have also been reported to cause illness in humans. Studies on the plasmid content of serovar E strains revealed the existence of a plasmid of approximately 70 kbp present in most of these strains. In this study we characterized the 70 kbp plasmids of seven biotype 2 strains isolated from seawater, diseased eels and wound infections in humans. We determined the exact size of the high molecular weight plasmids to be 68 kbp. A comparison o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The biotype 2 serovar E and serovar O3 strains harbor plasmids with different molecular weights (8,17,19). We further determined the location of each identified biotype 2-specific sequence in the genome of CECT4602 by Southern hybridization using total DNA and plasmid DNA, respectively, as the templates.…”
mentioning
confidence: 66%
“…The biotype 2 serovar E and serovar O3 strains harbor plasmids with different molecular weights (8,17,19). We further determined the location of each identified biotype 2-specific sequence in the genome of CECT4602 by Southern hybridization using total DNA and plasmid DNA, respectively, as the templates.…”
mentioning
confidence: 66%
“…The presence of plasmids of high M r in BT2 strains has previously been reported Høi et al, 1998;Lewin et al, 2000). In fact, three BT2-specific plasmidic sequences have been found by comparison of BT1 and BT2 genomes by subtractive hybridization (Lee et al, 2005).…”
Section: Discussionmentioning
confidence: 88%
“…Two previous findings, the presence of large plasmids in all BT2 strains (6,16,30) and the identification of BT2-specific plasmid DNA sequences found by SSH (28), suggested that the plasmids might be involved in virulence for eels. To confirm this, we selected two highly virulent serovar E strains, CECT4999 and CECT4602, that exhibited different plasmid profiles and determined the nucleotide sequences of their plasmids, followed by isolation of a plasmid-cured strain and testing of its virulence.…”
Section: Discussionmentioning
confidence: 99%
“…Further, these DNA sequences were all located in the plasmids, suggesting that the virulence for eels could be conferred by a plasmid. In fact, previous studies had shown that all BT2 strains harbored one or more plasmids of high molecular weight (6,22,30).The purpose of this study was to investigate the role of plasmids in the virulence of BT2 V. vulnificus for eels. Toward this end, we determined and analyzed the nucleotide se-* Corresponding author.…”
mentioning
confidence: 98%
See 1 more Smart Citation